The Performance of U.S. Equity Mutual Funds during the Recent Recession - Zhang, Qitao (2010)
The world economy is suffering under the financial crisis. The mutual fund market, one of the most popular investments, is worth to observe during the recent recession in order to provide some valuable information for investors to reconsider their investment strategies. In this paper, 180 actively managed U.S. equity mutual funds from 2004 to 2010 are selected as the sample data. It empirically examines the persistence performance of mutual funds within the period 2004 to 2007(bull) and 2007 to 2010(recession), plus tests the size effect in different periods by comparing Jensen’s Alpha, Treynor’s ratio and Sharpe’s ratio. The findings suggest performances of mutual funds are, on average, worse than S&P 500 in any sample periods; while mutual funds have a greater performance in bull rather than in recession. In addition, performances in different size funds are not much difference in any particular periods; whereas, the same size funds perform better in bull rather than in recession.